Engineering Education in the Rapidly Changing World: Rethinking the Vision for Higher Engineering Education | Second Revised Edition - Kamp, Aldert (none, 2023)
The first edition inspired many conversations about “The Future Engineer” at my home university and many partner universities and institutes abroad. The “Free Spirits” Think Tank of the 4TU.Centre of Engineering Education in the Netherlands, which investigates the rise of new engineering profiles in the coming 10 to 15 years and develops matching scenarios for campus education in 2030, has taken my vision as a source of inspiration. The numerous meetings and workshops I attended between engineering academics, industries and engineering consultancies in the Netherlands and abroad, and the conferences and panels of the global CDIO Initiative and the World Engineering Education Forum (WEEF) in Florence (2015) all discussed the subject of the engineer and industry of the future. They addressed the impact of the changing global economy, the fast pace of change, the limited shelf life of specialist knowledge, the university’s role in innovation, the need for an interdisciplinary mind-set, the global interconnectedness, the rise of machine intelligence and the use of open standards. These are all aspects that shape the rapidly changing world in which we live and in which we educate tomorrow’s engineers, who might be a different breed than the ones we have been educating over the past 50 years. These factors set the scene for the “why” and “what” of our future education.